Glycemic fluctuations, fatigue, and sleep disturbances in type 2 diabetes during ramadan fasting: A cross-sectional study. - Satwika Arya Pratama; Rudy Kurniawan; Hsiao-Yean Chiu; Hsuan-Ju Kuo; Emmanuel Ekpor; Po-Jen Kung; Safiruddin Al Baqi; Faizul Hasan; Debby Syahru Romadlon (PLoS ONE)
Background This study aimed to assess the prevalence of glycemic fluctuations, fatigue, and sleep disturbances during Ramadan, and to identify factors associated with hypoglycemia and hyperglycemia events in this period. Methods A cross-sectional study of 88 individuals with type 2 diabetes during Ramadan fasting from (08/03/2024) until (20/04/2024) was conducted. HbA1c levels before Ramadan were obtained from medical records. Participants monitored blood glucose twice daily (during the day and two hours after breaking fast). Blood glucose under 70 mg/dl was considered hypoglycemia, and over 200 mg/dl was hyperglycemia. Fatigue was thoroughly assessed using the Indonesian Multidimensional Fatigue Inventory-20 (IMFI-20), while the Pittsburgh Sleep Quality Index (PSQI) was utilized to evaluate sleep quality. In addition, data on sleep duration, as well as dietary habits during Ramadan, were also collected. Results A total of 88 patients with type 2 diabetes (mean age, 52.7 years) participated, predominantly female (68.2%) and married (63.6%). The study found a prevalence of 21.6% for hypoglycemia and 30.6% for hyperglycemia. Additionally, 30.7% of participants experienced fatigue, and 40.9% reported poor sleep quality. HbA1c levels before Ramadan and fatigue were significantly associated with both hypoglycemia and hyperglycemia (p <  0.05). Sleep quality was also significantly associated with hyperglycemia events (p <  0.05). Furthermore, sleep duration was significantly related to hyperglycemia events (p =  0.01). Meal timing, frequency, and dietary patterns during Ramadan were also found to be significantly associated with both hypoglycemia and hyperglycemia (both p <  0.05). Conclusion Hypoglycemia and hyperglycemia are common among people with type 2 diabetes during Ramadan. Fatigue and poor sleep quality were also widespread. Key factors linked to these glycemic fluctuations were pre-Ramadan HbA1c levels and fatigue, while sleep quality was particularly associated with hyperglycemia. These results highlight the need for personalized care to manage blood sugar levels and improve overall health during Ramadan. We recommend that healthcare providers advise patients with type 2 diabetes to aim for 7-8 hours of sleep per night to help control blood glucose levels. Additionally, having three meals a day (Suhoor, Iftar, and a post-Iftar snack) with low glycemic index foods can help maintain stable blood glucose and prevent both hypoglycemia and hyperglycemia during Ramadan.